The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2118/148130-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multirate Dual-Porosity Model for Improved Simulation of Fractured and Multiporosity Reservoirs

Abstract: A major part of the world's remaining oil reserves is in fractured carbonate reservoirs, which are dual-porosity (fracture-matrix) or multiporosity (fracture/vug/matrix) in nature. Fractured reservoirs suffer from poor recovery, high water cut, and generally low performance. They are modeled commonly by use of a dual-porosity approach, which assumes that the high-permeability fractures are mobile and low-permeability matrix is immobile. A single transfer function models the rate at which hydrocarbons migrate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…The most widely used are the Multi-Rate Mass Transfer (MRMT) and Continuous Time Random Walk (CTRW). MRMT is a non-local in time continuous formulation that simulates mass transfer between a mobile and multiple immobile regions by diffusive or first-order mass transfer terms (Benson and Meerschaert, 2009;Carrera et al, 1998;Donado et al, 2009;Fernandez-Garcia and Sanchez-Vila, 2015;Geiger et al, 2013;Gouze et al, 2008;Haggerty and Gorelick, 1995;Haggerty et al, 2000;Roth and Jury, 1993;Wang et al, 2005;Willmann et al, 2010;Zhang et al, 2007). Models similar to MRMT exist for diffusion from a fracture into the matrix of the rock (Cvetkovic et al, 1999;Gerke and van Genuchten, 1996;Grisak and Pickens, 1980;MaƂoszewski and Zuber, 1985;Moreno and Neretnieks, 1993;Shapiro, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used are the Multi-Rate Mass Transfer (MRMT) and Continuous Time Random Walk (CTRW). MRMT is a non-local in time continuous formulation that simulates mass transfer between a mobile and multiple immobile regions by diffusive or first-order mass transfer terms (Benson and Meerschaert, 2009;Carrera et al, 1998;Donado et al, 2009;Fernandez-Garcia and Sanchez-Vila, 2015;Geiger et al, 2013;Gouze et al, 2008;Haggerty and Gorelick, 1995;Haggerty et al, 2000;Roth and Jury, 1993;Wang et al, 2005;Willmann et al, 2010;Zhang et al, 2007). Models similar to MRMT exist for diffusion from a fracture into the matrix of the rock (Cvetkovic et al, 1999;Gerke and van Genuchten, 1996;Grisak and Pickens, 1980;MaƂoszewski and Zuber, 1985;Moreno and Neretnieks, 1993;Shapiro, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…First, the implementation of the LM-L 2 method is tested by comparing the obtained results to 2D benchmark results presented by Flemisch et al [20]. Benchmark 1, which was first introduced by Geiger et al [24], is chosen as a representative example for this study. Emphasis is placed on the validation of the presented method with reference results from Geiger et al [24], Flemisch et al [20], while results of alternative approaches can be found in the listed references.…”
Section: Benchmark -2dmentioning
confidence: 99%
“…Having a pure calcium carbonate system with no chemical heterogeneity, the partitioning of the porous medium is only due to the physical heterogeneity at pore scale (fracture/matrix), and therefore, no localization of reactions is assumed. We consider one immobile zone only, to align the formulation with the time‐dependent single‐rate mass transfer model as opposed to multiple rate mass transfer model where multiple mass transfer processes occur simultaneously in a porous medium (see, e.g., Fernandez‐Garcia & Sanchez‐Vila, ; Geiger et al, ; Maier et al, ; Soler‐Sagarra et al, ; Tecklenburg et al, ). As such equation (3) can be rewritten as ϕmrsans-serif-italicf,sans-serif-italicm∂csans-serif-italicA,sans-serif-italicm∂sans-serif-italict+ux∂csans-serif-italicA,sans-serif-italicm∂sans-serif-italicx+uz∂csans-serif-italicA,sans-serif-italicm∂sans-serif-italicz=ϕmsans-serif-italicD()∂2csans-serif-italicA,sans-serif-italicm∂x2+∂2csans-serif-italicA,sans-serif-italicm∂z2−α()csans-serif-italicA,sans-serif-italicm−csans-serif-italicA,sans-serif-italicim,sans-serif-italicj+rsans-serif-italicchem,sans-serif-italicA,sans-serif-italicm, ϕimrsans-serif-italicf,sans-serif-italicim∂csans-serif-italicA,sans-serif-italicim…”
Section: Simplified Co2 Reaction With Calcium Carbonatementioning
confidence: 99%
“…Having a pure calcium carbonate system with no chemical heterogeneity, the partitioning of the porous medium is only due to the physical heterogeneity at pore scale (fracture/matrix), and therefore, no localization of reactions is assumed. We consider one immobile zone only, to align the formulation with the time-dependent singlerate mass transfer model as opposed to multiple rate mass transfer model where multiple mass transfer processes occur simultaneously in a porous medium (see, e.g., Fernandez-Garcia & Sanchez-Vila, 2015; Geiger et al, 2013;Maier et al, 2013;Soler-Sagarra et al, 2016;Tecklenburg et al, 2016). As such equation (3) can be rewritten as…”
Section: Simplified Co 2 Reaction With Calcium Carbonatementioning
confidence: 99%